(3efJNH ef JGQjN GHf GdTMfIs - (3eMeO Hf CMeO Hf eMeO GdMUcaj GdeYQha HGHf GdefdG GdMdHjs
(3ChdgG (B:s
(3hHYO , agPg fHPI EfJNHJgG eeG GfJNHg GdYdGeI Rjf GdOjf CMeO Hf Ydj Hf MSjf Hf Ydj GdeYQha ef JGQjN GdYdGeI CbVi GdbVGI GHf GdhdjO GHf GdTMfI GdMdHj hbO LYdJgG SHYI YTQ HGHkG s
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B158 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs